The Persuasion in Joko Widodo’s Speech: A Comparison between the Indonesian Source Text and Its Annotated Translation in Mandarin - Adinda Natassa Valentine Hutabarat (Madah: Jurnal Bahasa dan Sastra, 2020)
AbstractThis study aims to describe persuasion strategies used by President Joko Widodo in his political speech that is delivered at the 2018 IMF-World Bank forum. The study is conducted by comparing the speech in bahasa Indonesia as the Source Text (ST) and its annotated Mandarin translations as the Target Text (TT). In order to describe Widodo’s persuasion strategies, micro and macro level analysis is applied in this study. The former refers to the speaker’s language skills and the translations; whilst the latter refers to the speaker-oriented context and situations-oriented contexts. The result of the study shows that: (i) The translation of Widodo’s speech text has persuasive features of metaphors and catchwords; (ii) The translation technique applied to these features is “equivalent”; (iii) These features were used to encourage the audience to pay attention to the contexts-oriented persuasive messages and to take actions accordingly. AbstrakKajian ini bertujuan untuk mendeskripsikan strategi persuasi Presiden Joko Widodo dalam pidato politis yang disampaikan pada pertemuan IMF-Bank Dunia tahun 2018. Kajian tersebut dilakukan dengan membandingkan Teks Sumber (TSu) bahasa Indonesia dan terjemahan beranotasi Teks Sasaran (TSa) bahasa Mandarin. Guna mendeskripsikan strategi persuasi tersebut, studi ini menggunakan analisis mikro dan makro. Analisis mikro merujuk pada analisis keterampilan bahasa dan terjemahannya. Analisis makro merujuk pada konteks pembicara dan konteks situasi. Hasil kajian ini menunjukkan bahwa: (i) Terjemahan teks pidato Widodo menggunakan fitur persuasi metafora dan catchwords; (ii) Teknik terjemahan yang diaplikasikan pada kedua fitur tersebut adalah “kesepadanan”; (iii) Fitur tersebut digunakan agar pembaca atau pendengar memfokuskan pada pesan persuasi yang berorientasi konteks, dan bertindak sesuai pesan persuasi tersebut.